2012
DOI: 10.1177/1468087412465378
|View full text |Cite
|
Sign up to set email alerts
|

Size-scaling effect on the velocity field of an internal combustion engine, part I: Bulk motion

Abstract: In-cylinder velocity measurements were acquired to study the bulk fluid motion in two geometrically scaled, two-valve, optically accessible, and single-cylinder research engines. Different port geometries (two), different port orientations (two), and both shrouded and nonshrouded intake valves were tested to vary the intake-generated flow. The engines were motored at speeds ranging from 300 to 1200 r/min for the larger engine and from 600 to 1800 r/min for the smaller engine. Prior to testing on the engines, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…One plausible scenario is that the individual-cycle swirl center location differs from the ensemble-mean location, and the flow may not be organized as a solid-body rotation on this cycle. 1 The presence of large regions of nearly uniform fluctuation velocity, as shown in Figure 7(a), also manifests itself as a long-range correlation of the velocity field, yielding longer integral length scales. In contrast, the spatial-mean velocity fluctuation field in Figure 7(b) shows smaller scale structures that resemble turbulent eddies and appear to have a random rotation direction.…”
Section: Spatial-average Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…One plausible scenario is that the individual-cycle swirl center location differs from the ensemble-mean location, and the flow may not be organized as a solid-body rotation on this cycle. 1 The presence of large regions of nearly uniform fluctuation velocity, as shown in Figure 7(a), also manifests itself as a long-range correlation of the velocity field, yielding longer integral length scales. In contrast, the spatial-mean velocity fluctuation field in Figure 7(b) shows smaller scale structures that resemble turbulent eddies and appear to have a random rotation direction.…”
Section: Spatial-average Analysismentioning
confidence: 95%
“…1 For the present results where the engines are precisely scaled, the geometric parameters cancel between the two engines, and since all the engine testing was performed with a constant intake temperature, the speed of sound was constant for all cases and is retained solely for dimensional reasons. The main advantage of Z is that it accounts for differences in the intake flow by means of the mass-weighted flow coefficient.…”
Section: Size Scalingmentioning
confidence: 99%
“…Although the similarity of engine performance and emissions can be achieved to some extent, as shown in the above literature review, the existing three scaling laws exhibit several weaknesses that should be further addressed. For example, the brake thermal efficiency (BTE) is difficult to be completely scaled due to the increased heat transfer loss 18,19 and friction loss 20,21 of small engine caused by the larger surface to volume ratio. In the previous study, the intake temperatures of the small engines were usually increased to compensate for the effect of larger heat transfer losses.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the S rule is more preferable in the LTC regimes, due to the identical timescale for chemical reactions. Recently, Heim and colleagues 12,13 investigated the similarity of turbulence properties in different size engines. They found that the swirl center locations are in nearly the same location between the large and small engines.…”
Section: Introductionmentioning
confidence: 99%